Effects of Isentropic Efficiencies on the Performance of Combined Cycle Power Plants - Ibrahim, Tamir K.; M. M., Rahman (Universiti Malaysia Pahang, 2015)
This study deals with modelling and performance enhancements of a combined cycle power plant. Several configurations of CCGT power plants are proposed by thermal analysis. The integrated model and simulation code for exploiting the performance of the CCGT power plant is developed utili zing MATLAB code. A different strategy for the CCGT power plant's operational modelling is suggested for power plant operation, to improve overall performance. The effect of is e ntropic efficiencies on the performance of the CCGT power plant is based on rea l CCGT power plants. An extensive thermodynamic analysis of the modifications of the most common configuration enhancements has been carried out. The simulati o n results for the HRSG configurations show that the maximum power output (1000 MW) occurred in th e supplementary triple - pressure reheat CCGT at high isentropic compressor efficiency. Furthermore, with the triple - pressure reheat CCGT and higher isentropic turbine efficiency the maximum overall efficiency was about 58.3%. In addition, the proposed CCGT system improved the thermal efficiency by 1.6% and the power output by 11.2%. Thus, the isentropic efficiencies and CCGT configurations have a strong influence on the overall performance of the CCGT